I "Sonetti et canzoni" di I. Sannazaro: un "liber" critico e militante (Quaderni di Gargnano, 2020)
Sannazaro devoted himself to vernacular poetry beyond his return from exile: this is attested by some testimonies contemporary to the poet, but also by some poems of the Sonetti et canzoni composed, or rewritten, in the first and second decade of the sixteenth century. The posthumous princeps of the Sonetti et canzoni testifies in fact a work dating back to the late '20s and, moreover, offers a songbook that, although not completely finished, nevertheless exhibits a cryptic but eloquent dialogue with the horizon marked by the Bembian prescriptions (and proscriptions). This is a refined communicative strategy, exhibited on several levels: from the graphic-phonetic and lexical ones to the syntactic and structural ones. Sannazaro, for this intent, inserts significant and calibrated dating within the Sonetti et canzoni, aiming to place the liber at a date prior to the beginning of the new century, with the related claim, therefore, of his early competence in Petrarch's code. But for his purpose he uses above all a particular linguistic patina (still visible in the Sonetti et canzoni despite the interventions of the editors) which ostentatiously wants to recall a tradition of the Fragmenta prior to the Cose volgari of 1501 and to the relative, canonizing, pruning operated by Bembo. Such a distance from the Aldina of 1501 and the intentional reference to the fifteenth-century tradition of Petrarch's opus are also measurable from a structural point of view: as attested by the precise connections that some of the opening and closing pieces of the Sonetti et canzoni deliberately create with a widespread fifteenth-century arrangement of the Fragmenta, also accepted by the princeps Vindelino of 1470 and by the incunabulum published in Naples in 1477 by Arnaldo da Bruxelles. La dedizione del Sannazaro allo scrittoio volgare si protrasse certamente oltre il ritorno dall’esilio: lo attestano alcune testimonianze coeve al poeta ma ancora alcuni tasselli dei Sonetti et canzoni composti, o riscritti, ben addentro il nuovo secolo. La postuma princeps conserva cioè traccia di un lavorio risalente agli ultimi anni ’20 ed accoglie anzi un liber che, seppur non ritoccato ad unguem, esibisce tuttavia un velato ma eloquente dialogo con l’orizzonte definito a quella data dalle prescrizioni (e proscrizioni) bembiane. Si tratta di una raffinata strategia comunicativa, esibita a più livelli: da quello grafico- fonetico e lessicale a quello sintattico e strutturale. Nella predisposizione di tale colloquio rientrano le datazioni emergenti dai Sonetti et canzoni, miranti a collocare il liber in data anteriore allo scoccare del nuovo secolo, con connessa rivendicazione, pertanto, della propria precoce competenza della tastiera petrarchesca. Ma a tale scopo concorre anche la peculiare patina linguistica dei Sonetti et canzoni (ancora visibile nonostante gli interventi dei curatori) che esibisce il palese richiamo ad una tradizione dei Fragmenta anteriore alle Cose volgari del 1501 e al relativo, canonizzante, sfrondamento operatovi dal Bembo. Tale presa di distanza dall’Aldina del 1501 e il voluto rinvio ad alcune filiere  quattrocentesche dell’opus petrarchesco risultano misurabili nei Sonetti et canzoni anche sotto il profilo strutturale: come attestano i precisi rimandi di alcuni tasselli incipitari e di chiusa ad un diffuso, nel ‘400, ordinamento dei Fragmenta, presente tra l’altro nella princeps Vindelino del 1470 e nell’incunabulo edito a Napoli nel 1477 per i tipi di Arnaldo da Bruxelles.
Keywords: Sannazaro; Sonetti et canzoni; canzoniere; struttura; Petrarca